Optimization Of Immunoillstochemistry: Testing For Mlhl And Msh2 Proteins In Colon Tissue - Muhsain, Siti Nur Fadzilah (2005)
Microsatellite instability (MSI) accounts for the development of about 15% of all colorectal cancers. It is characterized by mutations in mismatch repair (MMR) genes that render cells unable to detect errors during DNA replication. Mutations in the MMR genes, MLHl and MSH2 are responsible for the majority of CRC with MSI. These MMR proteins can be detected by immunohistochemistry (lllC). IHC has proved sensitive and specific when compared to molecular analysis of MSI. Nevertheless, generally, there is no published literature as yet on studies of MSI in Malaysia, and specifically using lliC. Before any lliC staining procedure can be done, it has to be optimized. In this study, attempts were made to optimize rnc staining of MLHl and MSH2 proteins using polyclonal rabbit antibody by Biovision on formalin-fixed paraffm-embedded sections of normal colon, taken from resected margins of colectomy specimens. Either Vectastain Elite ABC Kit or DAKO En Vision Kit was used as secondary detection system. The staining procedure was done using different dilutions of the primary antibodies and incubated for different durations at different temperatures. Antigen retrieval procedures were introduced using citrate buffer pH 6 or Tris-EDTA buffer pH 9. The results showed that incubation of sections at room temperature using different dilutions of antibody failed to produce any nuclear staining. Staining with DAKO En Vision was still unsatisfactory, although background staining was reduced. Introduction of antigen retrieval procedure using microwave did not improve results. When incubated at 4°C, non-specific background staining was produced.